Graph and chart aesthetics for experts and laymen in design: The role of familiarity and perceived ease of use. (July 2016) - Quispel, Annemarie; Maes, Alfons; Schilperoord, Joost
We investigated the relationship between familiarity, perceived ease of use, and attractiveness of graph designs in two target groups: experts and laymen in design. In the first study, we presented them with a variety of more or less common graph designs and asked them without any additional task to evaluate their familiarity, attractiveness, and perceived ease of use. They judged the familiarity and ease of use of the graphs similarly, but they differed in their attractiveness judgments. Familiarity and perceived ease of use appeared to predict attractiveness, but stronger for laymen than for designers. Laymen are attracted to designs they perceive as familiar and easy to use. Designers are attracted to designs between familiar and novel. In the second study, we asked designers and laymen to first perform an information retrieval task with the same graphs and then rate their attractiveness. Laymen's appreciations remained the same, but the designers' judgments of attractiveness were different from those in study 1. Correlational analyses suggest that their attractiveness judgments after use were affected not by actual usability but by perceived ease of use of the graphs.